2019
DOI: 10.21203/rs.2.10905/v4
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

AMAFRICA, a patient-navigator program for accompanying lymphoma patients during chemotherapy in Ivory Coast: a prospective randomized study

Abstract: Background Previous studies have indicated that accompanying socially undeserved cancer patients through Patient Navigator (PN) or PN-derived procedures improves therapy management and reassurance. At the Cancer Institute of Toulouse-Oncopole (France), we have implemented AMA (Ambulatory Medical Assistance), a PN-based procedure adapted for malignant lymphoma (ML) patients under therapy. We found that AMA improve adherence to chemotherapy and safety. In low-middle income countries (LMIC), refusal and abandonme… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…In Malawi, we have shown that low cancer health literacy is a leading cause of treatment abandonment among children and adolescents, and this has also been observed elsewhere in adults and children in SSA. 1,2,[5][6][7] In high-income settings, standardized patient cancer education is often facilitated through a comprehensive educational session by a nurse educator at the time of diagnosis. Educational videos and other technologybased educational interventions for cancer-specific patient education have been successful in these settings.…”
Section: Introductionmentioning
confidence: 99%
“…In Malawi, we have shown that low cancer health literacy is a leading cause of treatment abandonment among children and adolescents, and this has also been observed elsewhere in adults and children in SSA. 1,2,[5][6][7] In high-income settings, standardized patient cancer education is often facilitated through a comprehensive educational session by a nurse educator at the time of diagnosis. Educational videos and other technologybased educational interventions for cancer-specific patient education have been successful in these settings.…”
Section: Introductionmentioning
confidence: 99%